A Framework for An LTS Semantics for PROMELA - Suprapto, Suprapto (2011)
A high-level specification language PROMELA can be used not only to model interactions that occur in distributed or reactive systems, but also to express requirements of logical correctness about those interactions. Several approaches to a formal semantics for PROMELA have been presented, ranging from the less complete formal semantics to the more complete ones. This paper presents a significantly different approach to provide a formal semantics for PROMELA model, namely by an operational semantics given as a set of Structured Operational Semantics (SOS) rules. The operational semantics of a PROMELA statement with variables and channels is given by a program graph. The program graphs for the processes of a PROMELA model constitute a channel system. Finally, the transition system semantics for channel systems yields a transition system that formalizes the stepwise behavior of the PROMELA model.